Effect of dairy products intake in women with premenstrual syndrome: a randomized controlled trial: Dairy products intake in women with premenstrual syndrome - Yurt, Merve; Mercanlıgil, Seyit Mehmet; Kabaran, Seray (Progress in Nutrition, 2020)
Aim: This study was planned and conducted to investigate the effects of adequate dairy products, at least 3 portions, and calcium intake on Premenstrual Syndrome (PMS) symptoms in women with PMS who have inadequate calcium intake. Methods: Thirty-one women, aged between 20-28 years who were diagnosed with PMS had participated. All women had inadequate calcium intake and regular menstrual cycles. These participants were randomly allocated into two groups, an intervention (n=16) group and a control (n=15) group. Itwas ensured that the intervention group consumed foods containing at least 1000 mg calcium for two months. Turkish kasseri cheese (50 g) which is made from cow’s milk was provided to the intervention group and theywere informed to consume at least 400 ml of milk and 150 g of yogurt every day for two months. No specificdiet was recommended to the control group. The Premenstrual Syndrome Scale (PMSS) and the Short Formof Quality of Life Scale were administered at the baseline and after the study. Independent t-test and Mann-Whitney-U test were used for group comparisons according to data normality. Results: No significant differencein PMSS scores, physical functions and mental health scores on the SF-36 quality of life scale and daily calcium intake between the intervention (500.9±114.6 mg) and the control groups (511.3±149.2 mg) at baseline assessment (p>0.05). The intervention group’s total PMSS post-intervention (104.8±21.5) score was found to be significantly lower than their baseline scores (151.9±15.4) (p<0.05). The intervention group’s physical functions (47.9±8.0) and mental health (48.6±6.9) post-intervention scores on the SF-36 quality of life scale were found to be significantly higher than their baseline scores (41.2±10.7 and 45.0±10.7 respectively) (p<0.05). Conclusion: These results indicate that sufficient dairy and calcium intake affects women’s PMS symptoms and improves the quality of life.